2007
DOI: 10.1002/crat.200610842
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of recovery mechanism of impurity effect by the addition of EDTA

Abstract: The impurity effect by trivalent metal ion such as Al 3+ , Fe 3+ and Cr 3+ during crystal growth of KDP is reasonably well documented. If a metal ion is adsorbed onto the crystal surface, it prevents the step propagation relevant to the crystal growth rate. However, this impurity adsorption mechanism is still not well understood. Recently, in our work on the addition of chelate agents, a recovery effect of the metal ion adsorption was discovered. However, its recovery mechanism is not clearly understood both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…14) In a previous report, it has been shown that impurities attach to the crystal surface and thereby interrupt crystal growth. 7,[15][16][17][18] For example, it has been shown that many kinds of substances (metal ions, proteins, etc.) inhibit the nucleation and crystal growth of hydroxyapatite (HAP).…”
Section: Discussionmentioning
confidence: 99%
“…14) In a previous report, it has been shown that impurities attach to the crystal surface and thereby interrupt crystal growth. 7,[15][16][17][18] For example, it has been shown that many kinds of substances (metal ions, proteins, etc.) inhibit the nucleation and crystal growth of hydroxyapatite (HAP).…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of the distribution of these impurities in the pyramidal and prismatic sectors of KDP agree well with Asakuma's theory. 6 The crystals were cut and oriented with high precision to obtain rectangular samples for EPR and optical absorption experiments. The EPR sample was rectangular with dimensions of 3 × 3 × 3.3 mm 3 along with the crystal a, b, and c axis.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] However, the behaviour of the impurity ions, once they have entered the crystal, is not yet completely clarified, even for divalent (e.g., Cu 2+ , Co 2+ , Ba 2+ , Fe 2+ ) and trivalent metal ions (e.g., Fe 3+ , Cr 3+ , Al 3+ ), which are currently considered to have the most significant influence. [6][7][8][9] The structure of the KDP crystals at room temperature belongs to the tetragonal crystal system, and the space group is I4 ¯2d. The cell parameters are a = b = 0.7453 nm and c = 0.6974 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDTA(ethylene-diamine-tetra-acetic acid, ) [6,7] (Sunset Yellow, Brilliant blue etc.) (100),(101) KDP [8][9][10]] KDP (Gaussian R 03W Ver.6, Gaussian Inc.) [11] (1)…”
mentioning
confidence: 99%